The Mediating Role of Teacher Engagement in the Effect of Green Technology Adoption and Pedagogical Technostress on Green Teaching Perfomance - Fitri Rezeki; Yunata Kandhias Akbar; Hardiansyah; Muhammad Sapruwan (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to analyze the influence of Green Technology Adoption and Pedagogical Technostress on Green Teaching Performance, with Teacher Engagement as a mediating variable. The quantitative survey was conducted 87 teachers who had used digital technology in the learning process. The study employed saturation sampling, in which the entire population was included as the research sample. Data analysis was conducted using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The results indicate that Green Technology Adoption has a positive and significant effect on Green Teaching Performance and Teacher Engagement. Pedagogical Technostress also has a positive and significant effect on Green Teaching Performance and Teacher Engagement. Additionally, Teacher Engagement was found to have a positive and significant effect on Green Teaching Performance. The mediation test results indicate that Teacher Engagement mediates the effects of Green Technology Adoption and Pedagogical Technostress on Green Teaching Performance. An R-square value of 0.840 indicates that the model has a strong ability to explain the variation in Green Teaching Performance. These findings confirm that the success of green technology-based learning is determined not only by the use of technology but also by teacher engagement in the learning process.